Persepsi Ulama Banjarmasin terhadap Produk BNI Emas iB Hasanah BNI Syariah - Komarudin, Parman (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2021)
This study aims to analyze the perception of the Banjarmasin ulema towards the BNI Emas iB Hasanah product offered by BNI Syariah. This research is qualitative field research with a case study approach. The authors collected primary data through structured interviews with five Banjarmasin scholars, to be analyzed using descriptive techniques. The results showed that one of the five scholars who became the object of this research stated that the product was haram because gold is a usury item that cannot be the object of buying and selling installments, while four of the five scholars agreed that the use of installment buying and selling contracts in gold transactions as practiced by BNI Syariah on the BNI Emas iB Hasanah product, the law is permissible because the gold in this product is a commodity item that can be an object of buying and selling according to the direction of the DSN Fatwa Number 77 of 2010 concerning the Sale and Purchase of Gold in Cashless.Keywords: BNI Syariah; BNI Emas iB Hasanah; Banjarmasin Ulama's Perception.